Pengaruh Konten Linkedin Wulan Budi Asmoro terhadap Personal Branding Followersnya - Fadhil Aiman; Ami Saptiyono (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The rapid growth of social media, particularly LinkedIn, has created new opportunities for individuals to build personal branding. However, previous studies have mostly emphasized LinkedIn’s role as a professional networking platform without thoroughly examining the impact of specific content on users’ self-image development. This limitation encourages the present study to specifically investigate the influence of Wulan Budi Asmoro’s LinkedIn content on her followers’ personal branding. The objective of this study is to determine how consistent and educational content can shape followers’ perceptions and strategies in developing their personal branding. This research employed a quantitative approach with probability sampling, involving 100 respondents selected from more than 21,000 followers. The research instrument was tested for validity and reliability, with Cronbach’s Alpha values exceeding 0.60. Simple linear regression analysis revealed that Wulan Budi Asmoro’s LinkedIn content has a significant influence on personal branding, with a coefficient of determination of 90.3%, while the remaining 9.7% is influenced by other external factors. These findings confirm that consistent, relevant, and valuable social media content serves as a strong stimulus in shaping personal branding, in line with the Stimulus-Organism-Response (S-O-R) theory. The study concludes that personal branding strategies can be optimized through the effective use of targeted and consistent LinkedIn content